IMPROVING STUDENTS’ PRONUNCIATION ABILITY USING ENGLISH SONGS AT THE ELEVENTH GRADE OF SMAN 10 JENEPONTO - Muhmalia, Resky Ananda; Atmowardoyo, Haryanto; Sakkir, Geminastiti (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
The purpose of this research was to ascertain how students in SMAN 10 Jeneponto's eleventh grade may improve their pronunciation ability by employing English songs. This research used a pre-experimental design and a quantitative methodology. The eleventh grade students of SMAN 10 Jeneponto comprise the population of this research, while the sample consisted of 33 students in class XI.3. Data were gathered using pre- and post-testing. The analysis's findings indicate that the post-test mean score was 72.96 in the "good" classification and the mean pre-test score was 39.42 in the "very poor" classification. The probability value (sig. 2-tailed) = 0.000 is below the significance level of 0.05. Pronunciation abilities in grade eleven of SMAN 10 Jeneponto. According to the investigation, the hypothesis H0 is rejected and H1 is supported. The researcher came to the conclusion that using English songs helped students in the eleventh grade of SMAN 10 Jeneponto pronounce words more correctly based on the results of the data analysis. Keywords: English Song, Pronunciation Ability.